Women's stories in community-based post disaster responses in the Philippines (Compendium of Human Ecology Researches in the Philippines, 2003)
This paper reinforced the efforts to integrate gender perspective in disaster risk management through analysis of selective women's narratives of disaster. The women's stories in post-disaster illuminate the gendered nature of disaster experience. Women bear multiple layers of vulnerability (gender, class, ethnicity and age) that increase their risks to disaster. For instance, women's limited power to in decision making at home constraint women's contributions to risk reduction. Men and women are affected differently by disasters (e.g. women's reproductive needs as usually not met during emergency situations). Women have different priorities from men, during disasters (e.g. men spend more time in repair and construction while women attend to children, secure food, etc.). Furthermore women, exhibit apparent capacities and multiple roles during